The Routledge handbook of comparative world rhetorics : studies in the history, application, and teaching of rhetoric beyond traditional Greco-Roman contexts /: studies in the history, application, and teaching of rhetoric beyond traditional Greco-Roman contexts. (2020) - Unknown
No abstract available